Dysfunctional Breathing in Children and Adults With Asthma - Connett, Gary J.; Thomas, Mike (Frontiers in Pediatrics, 2018)
Asthma occurs across the life course. Its optimal treatment includes the use of personalised management plans that recognise the importance of co-morbidities including so-called ‘dysfunctional breathing’. Such symptoms can arise as a result of induced laryngeal obstruction (ILO) or alterations in the mechanics of normal breathing called breathing pattern disorders. Whilst these two types of breathing abnormalities might be related, studies tend to focus on only one of them and do not consider their relationship. Evidence for these problems amongst childhood asthmatics is largely anecdotal. They seem rare in early childhood. Both types are more frequently recognised in the second decade of life and girls are affected ore often. These observations tantalisingly parallel epidemiological studies characterising the increasing prevalence and severity of asthma that also occurs amongst females after puberty. Exercise ILO is more common amongst adolescents and young adults. It should be properly delineated as it might be causally related to specific treatable factors. More severe ILO occurring at rest and breathing pattern disorders are more likely to be occurring within a psychological paradigm. Dysfunctional breathing is associated with asthma morbidity through a number of potential mechanisms. These include anxiety induced breathing pattern disorders and the enhanced perception of subsequent symptoms, cooling and drying of the airways from hyperventilation induced hyperresponsiveness and a direct effect of emotional stimuli on airways constriction via cholinergic pathways. Hyperventilation is the most common breathing pattern disorder amongst adults. Although not validated for use in asthma, the Nijmegen questionnaire has been used to characterise this problem. Studies show higher scores amongst women, those with poorly controlled asthma and those with psychiatric problems. Evidence that treatment with breathing retraining techniques is effective in a primary care population including all types of asthmatics suggests the problem might be more ubiquitous than just these high-risk groups. Future challenges include the need for studies characterising all types of dysfunctional breathing in paediatric and adult patient cohorts and clearly defined, age appropriate, interventional studies. Clinicians caring for asthmatics in all age groups need to be aware of these co-morbidities and routinely ask about symptoms that suggest these problems.